Caracterização dos gastos em P&D da Lei de Informática no Pólo Industrial de Manaus 1996-2006 - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
The main objective of the research was to characterize the expenditure on R&D typifying by categories and behaviors of its actors (companies, institutes and part government, FNDCT) in which LI s systematic, where companies producing BIT have an obligation to invest in R&D resources . The research occurred from 1996 to 2006, in which, from the results established a discussion about the theory of innovation territorial basis of GREMI (Groupe Européen de Recherche sur les Mileux Innovateurs) with complement of the theories of Porter (Solution diamond and five forces model), and also make use of the PIM and BIT literature and other more specific elements that reinforce a dynamic indication of the PIM that shows structural elements of an economy grounded in innovation in territorial basis. The results provided an overview of distributions about the resources for R&D performed in Manaus in which one might observe a profile of incremental innovation process developed predominantly by private institutions sectors, whose rise of resources, in most cases, is foreign. The research shows features of PIM through the analysis of types of innovative environments (GREMI), featuring under the light of this theory, observe the reality of the local territory where is studied, shows eventually the characteristics of an Industrial District (not marshaliano) and eventually an innovative environment.
Keywords: Pesquisa e Desenvolvimento (P&D); Desenvolvimento Regional; Política de Informática - Polo Industrial de Manaus; Polo Industrial de Manaus - PIM; CIÊNCIAS SOCIAIS APLICADAS